Estudio de factibilidad para del procesamiento de aceite y leche de coco, en la Parroquia Borbon – Esmeraldas, 2020 - Perlaza Paredes, Derian Patricio (2021)
This research was aimed to determine the operational viability of a plant, based on the development of a feasibility study for the processing of Coconut Oil and Milk, in the Parish Borbón - Esmeraldas 2020. The direction of the analyzed products had as a segment 54.7% of the urban population of the province of Esmeraldas with ages between 20-59 years who established with the results of the surveys that they would like a 500 ml presentation for consumption. When analyzing the processor's location, the criteria taken into account were the proximity of raw materials, access roads availability, proximity to markets, taxes, and municipal licenses. To evaluate the viability of the project, the necessary values for the assembly and start-up of the Coconut Oil and Milk processor were quantitatively determined, requiring an investment of $ 93,175.41, of which 50% was equity capital and 50% % remaining through a bank loan with an interest rate of 8.37%. Another important aspect is the financial evaluation that carrying out the calculations, an NPV of $ 186,090.64 was obtained, with an IRR of 63.7%, its recovery period for the PRI investment was one year, six months, and five days.